SUPPORTIVE THERAPY OF PATIENTS WITH ATOPIC CHEILITIS - Ilenko, N.M.; Nikolishyna, E.V.; Marchenko, A.V.; Lytovchenko, I.Yu.; Ilenko-Lobach, N.V.; Nikolishyn, I.A.; Chechotina, S.Yu. (World of Medicine and Biology, 2023)
Currently, it is relevant to substantiate and implement methods of maintenance therapy for patients with atopic cheilitis using various groups of moisturizing agents that have a softening effect, stimulate epithelization processes, and eliminate the negative consequences of the disease. The purpose of the study was to substantiate the maintenance therapy in patients with atopic cheilitis using emollients. The study was based on the results of examination and treatment of 19 patients with atopic cheilitis, 12 (63 %) women and 7 (37 %) men, aged 20–36 years. To conduct a clinical study, patients were divided into two groups: 11 people (58 %) with a mild course of the disease, 8 people (42 %) with an average course of atopic cheilitis. Supportive therapy is a necessary step in the complex treatment of patients with atopic cheilitis. Differentiated use of emollients allows 79 % of patients to obtain positive treatment results on the 10th day. The proposed scheme of maintenance therapy can be recommended for use in therapeutic dentistry. Adherence to the principle of participation in the development of an individual course of treatment for atopic cheilitis helps to increase the patient's compliance and, ultimately, his satisfaction with the treatment. Only such a comprehensive approach will help maintain a relatively high quality of life for patients and improve the prognosis for atopic cheilitis.
Keywords: atopy; red rim of the lips; emollients